The aesthetic and the ethical: the dialogue between religious belief and literary form in D.H. Lawrence and T.S. Eliot - Rayment, Andrew David (2006)
This is a cross-disciplinary investigation that seeks to read some of the representative works of Eliot and of Lawrence as viewed through the critical lens of Soren Kierkegaard's authorship, its strategies and preoccupations. The third arrival in the earlier development of my theoretical project of cross-reading, and not an ascertainably direct influence, Kierkegaard soon became the dominant maieutic presence in my thesis, a fact that is deliberately signalled by the explicit reference to his Life Stages that my title makes. Some of SK's major concerns were indeed shared, idiosyncratically, by the two later writers, each in his distinct biographical, cultural and historical context. There is little undisputed and ascertainable evidence for any conscious direct influence of Kierkegaard on Eliot and still less so of Kierkegaard on Lawrence, but there are thematic, literary and, I will argue, significant diagnostic points of contact and mutual illumination. As Michael Bell did with Lawrence and Heidegger, beginning with Cassirer (Bell 1991: 3-4,6-10), in the same manner I read Kierkegaard as an 'explicatory parallel' to Lawrence and Eliot, as an aid to clarify and to 'bring out the internal complexity and cogency of ... [each man's] ... conception.' I believe this to be an academically valid and illuminative approach to themes of continuing significance.